The accumulation of capital - Luxemburg, Rosa, 1871-1919. (London ; New York : Routledge, 2003)
The book remains one of the masterpieces of socialist literature. Taking Marx as her starting point, the author offers an independent and fiercely critical explanation of the economic and political consequences of capitalism in the context of the turbulent times in which she lived, reinterpreting events in the United States, Europe, China, Russia and the British Empire. Many today believe there is no alternative to global capitalism. This book is a timely and forceful statement of an opposing view.
Originally published: London : Routledge & Kegan Paul, 1951.
Includes bibliographical references and index.
gau 13/06/14
Loans
Keywords: Capitalism; Saving and investment; Imperialism; Socialism